Bioprinting: 3D Bioprinting: from Benches to Translational Applications (Small 23/2019). Issue 23 (7th June 2019) - Heinrich, Marcel Alexander; Liu, Wanjun; Jimenez, Andrea; Yang, Jingzhou; Akpek, Ali; Liu, Xiao; Pi, Qingmeng; Mu, Xuan; Hu, Ning; Schiffelers, Raymond Michel; Prakash, Jai; Xie, Jingwei; et al.
Abstract : In article number1805510, Yu Shrike Zhang and co‐workers systematically review the history of 3D bioprinting and its recent advances in instrumentation and methods. The requirements for bioinks and cells to achieve optimal fabrication of biomimetic constructs, emerging evolutions and future directions of bioprinting, translational potential of bioprinting and bioprinted tissues of various categories, and exemplary commercially available bioprinting platforms are further discussed.